Seed dispersal by the brown bear in a mixed temperate forest: fruit type matters - Tavşanoğlu, Çağatay; Kazancı, Duygu Deniz; Soyumert, Anıl; Ertürk, Alper; Değirmenci, Cihan Ünal (Springer Science and Business Media LLC, 2021)
The brown bear (Ursus arctos L.) is an omnivorous large mammal that has an essential function in many ecosystems as a seed disperser. We studied the brown bear’s role as a seed dispersal agent in a mixed temperate forest in northern Anatolia, Turkey. We collected 197 fecal samples from the field during the brown bear’s active period for two consecutive years. We extracted seeds of 34 plant taxa from fecal samples. Among these taxa, 29 had intact seeds, whereas seeds of 5 were found to be entirely or mostly physically damaged. Damaged seeds belonged to fruits of acorn, capsule, nut, and drupe-like nut types, while no or few seeds from fleshy fruits such as berry, drupe, pome, and rosehip types had damage. Seeds from pome type fruits of Malus sylvestris and Pyrus elaeagnifolia had a higher germination percentage in feces than in the control (fresh seeds collected from the field), but that was quite the opposite in berries of Lonicera caucasica and Vaccinium arctostaphylos. No difference in germination percentage was found between feces and control groups in seeds from rosehips. Our results reveal that seeds of several species found in the study area are dispersed by the brown bear, especially those with fleshy fruits (e.g., Rosaceae members). In this study, we established the role of the brown bear as a seed dispersal agent in northern Anatolian mixed temperate forests. Our study suggests that fruit type is a determinant of the success of endozoochorous seed dispersal by the brown bear.
Keywords: 15. Life on land